Cyber security in the Gulf Cooperation Council states Froma Contenmporary geopolitical perspective - Ahmed.H. A; Suad.A. M (مجلة جامعة الأنبار للعلوم الإنسانية, 2020)
One of the national security policy of countries is Cyber security, many countries utilize their capacities that cyberspace provides for the considerations of security and military strength in which makes it to be included in its strategic calculations, the aim of this research is to study the geopolitics of cyber security for the Gulf Cooperation Council states as well as the most important owned pillars of cyber power by these countries. The problem of this study is; do the GCC countries possess the cyber power foundations that qualify them to adopt cyber deterrence strategies in the face of cyber-attacks. The outcomes of this research illustrate that the issue of cyber security has become a top priority for the national security issues for the Cooperation Council countries due to be safe from cyber threats, as can be realized that the high frequency of cyber-attacks in addition to the enlarged war against the Gulf Cooperation Council states through international information networks, this lets it to face threat to their economic, political and military security